Cancer immunoediting from immune surveillance to immune escape - Kim, Ryungsa (Blackwell Science Inc, 2007)
Cancer immune surveillance is considered to be an important host protection process to inhibit carcinogenesis and to maintain cellular homeostasis. In the interaction of host and tumour cells, three essential phases have been proposed: elimination, equilibrium and escape, which are designated the ‘three E’s'. Several immune effector cells and secreted cytokines play a critical role in pursuing each process. Nascent transformed cells can initially be eliminated by an innate immune response such as by natural killer cells. During tumour progression, even though an adaptive immune response can be provoked by antigen-specific T cells, immune selection produces tumour cell variants that lose major histocompatibility complex class I and II antigens and decreases amounts of tumour antigens in the equilibrium phase. Furthermore, tumour-derived soluble factors facilitate the escape from immune attack, allowing progression and metastasis. In this review, the central roles of effector cells and cytokines in tumour immunity, and the escape mechanisms of tumour cells during tumour progression are discussed.